Compositional change of gut microbiome and osteocalcin expressing endothelial progenitor cells in patients with coronary artery disease. - Takumi Toya (Public Library of Science (PLoS), 2021)
Osteogenic endothelial progenitor cells (EPCs) contribute to impaired endothelial repair and promote coronary artery disease (CAD) and vascular calcification. Immature EPCs expressing osteocalcin (OCN) has been linked to unstable CAD; however, phenotypic regulation of OCN-expressing EPCs is not understood. We hypothesized that gut-microbiome derived pro-inflammatory substance, trimethylamine N-oxide (TMAO) might be associated with mobilization of OCN-expressing EPCs. This study aimed to investigate the association between dysbiosis, TMAO, and circulating mature and immature OCN-expressing EPCs levels in patients with and without CAD. We included 202 patients (CAD N = 88; no CAD N = 114) who underwent assessment of EPCs using flow cytometry and gut microbiome composition. Mature and immature EPCs co-staining for OCN were identified using cell surface markers as CD34+/CD133-/kinase insert domain receptor (KDR)+ and CD34-/CD133+/KDR+ cells, respectively. The number of observed operational taxonomy units (OTU), index of microbial richness, was used to identify patients with dysbiosis. The number of immature OCN-expressing EPCs were higher in patients with CAD or dysbiosis than patients without. TMAO levels were not associated with circulating levels of OCN-expressing EPCs. The relative abundance of Ruminococcus gnavus was moderately correlated with circulating levels of immature OCN-expressing EPCs, especially in diabetic patients. Gut dysbiosis was associated with increased levels of TMAO, immature OCN-expressing EPCs, and CAD. The relative abundance of Ruminococcus gnavus was correlated with immature OCN-expressing EPCs, suggesting that the harmful effects of immature OCN-expressing EPCs on CAD and potentially vascular calcification might be mediated by gut microbiome-derived systemic inflammation.